Guidelines for the genetic diagnosis of hereditary recurrent fevers. Issue 10 (1st June 2012) - Shinar, Y; Obici, L; Aksentijevich, I; Bennetts, B; Austrup, F; Ceccherini, I; Costa, J M; De Leener, A; Gattorno, M; Kania, U; Kone-Paut, I; Lezer, S; et al.
Abstract : Hereditary recurrent fevers (HRFs) are a group of monogenic autoinflammatory diseases characterised by recurrent bouts of fever and serosal inflammation that are caused by pathogenic variants in genes important for the regulation of innate immunity. Discovery of the molecular defects responsible for these diseases has initiated genetic diagnostics in many countries around the world, including the Middle East, Europe, USA, Japan and Australia. However, diverse testing methods and reporting practices are employed and there is a clear need for consensus guidelines for HRF genetic testing. Draft guidelines were prepared based on current practice deduced from previous HRF external quality assurance schemes and data from the literature. The draft document was disseminated through the European Molecular Genetics Quality Network for broader consultation and amendment. A workshop was held in Bruges (Belgium) on 18 and 19 September 2011 to ratify the draft and obtain a final consensus document. An agreed set of best practice guidelines was proposed for genetic diagnostic testing of HRFs, for reporting the genetic results and for defining their clinical significance.